Fracture-resistant cement and preparation method thereof
By adding a specific proportion of modifiers and sulfaluminate cement, gypsum and calcium oxide to the cement, ettringite whiskers in situ, solving the problem of low flexural strength of traditional cement and achieving efficient structural regulation and performance improvement.
Patent Information
- Application Number
- CN202510488949.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2045-04-18
AI Technical Summary
The existing traditional cement has low flexural strength and is prone to cracking and failure under the tensile stress generated during shrinkage, making it difficult to meet the construction needs of high durability and long service life.
Modifiers are prepared by anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano SiO2 of a specific mass ratio, and sulfoaluminate cement, gypsum and calcium oxide are added to the flexural cement. The three react in situ to form ettringite whiskers and are evenly dispersed in the silicate cement matrix.
It significantly improves the flexural and compressive properties of cement, achieves good structural regulation, and enhances the early strength and low temperature resistance of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement materials, and in particular relates to flexural-resistant cement and a preparation method thereof. Background Art
[0002] Cement, also known as cement, red lime, and red soil, is a powdery hydraulic inorganic cementitious material that solidifies and hardens when mixed with water. It is usually not used alone, but is used to combine with sand and gravel (aggregates) to form mortar or concrete. The main raw material of cement is lime or calcium silicate. After hardening, it can resist the erosion of fresh water or salt water. As the main cementitious material component of concrete and cement mortar materials widely used in construction, bridges, water conservancy and national defense, its performance directly determines the performance of concrete and cement mortar materials. However, due to its low flexural strength, the existing traditional cement is easily cracked and damaged by the tensile stress generated during the shrinkage process during use, and it is increasingly difficult to meet the development needs of high durability and long service life of concrete buildings.
[0003] Patent CN109678402B discloses a preparation method and formula of a high-compression and high-flexural silicate cement composite material, which uses the synergistic effect of micron-level green silicon carbide and micro steel fiber to improve the composite material mixed with G-level oil well cement, ultrafine cement, and extra-fine cement. However, the compatibility of silicon carbide with micro steel fiber and cement system in the invention is not good, and the long-term mechanical properties of cement composite materials need to be further improved.
[0004] Patent CN110436801B discloses a high-flexural composite silicate cement and a preparation method thereof, wherein the high-flexural composite silicate cement is made from the following raw materials in parts by weight: 35-65 parts of silicate cement clinker, 17.5-40 parts of calcined clay, 10-22.5 parts of limestone, and 1.5-5 parts of gypsum. Although the cement in the invention improves the flexural strength to a certain extent, its 28d flexural strength can only reach 10.2MPa. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a flexural-resistant cement and a preparation method thereof, wherein the flexural-resistant cement has both excellent flexural and compressive properties.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a flexural cement, which comprises the following components in parts by weight: 55-80 parts of compound cement, 20-50 parts of gypsum, 5-15 parts of calcium oxide, 50-60 parts of fly ash and 4-8 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a mass ratio of 4-8:3-5:1.
[0007] What surprised the inventors of the present invention is that in the flexural cement system of the present invention, sulphoaluminate cement, gypsum and calcium oxide react with each other to generate ettringite whiskers in situ, and these whiskers are evenly dispersed in the silicate cement matrix and tightly combined with the matrix, promoting the development of its strength, thereby improving the flexural performance of the material. In addition, the inventors also found that in the cement system of the present invention, the content of ettringite whiskers generated in situ needs to be strictly controlled. If the whiskers are excessively generated, the flexural strength of the cement will be reduced. This is because the generation of excessive whiskers will cause the matrix to bulge and crack, resulting in microcracks in the matrix, which reduces the flexural performance of the material.
[0008] In the present invention, in the flexural cement, the weight of the composite cement is 55-80 parts. It can be understood that the weight can be any specific value of 55, 60, 65, 70, 75, and 80 parts, or any value within the range of 55-80 parts. In the present invention, the composite cement is a silicate cement and a sulphoaluminate cement in a weight ratio of 13-25:1. It can be understood that the weight ratio can be any specific value of 13:1, 18:1, 23:1, and 25:1, or any value within the range of 13-25:1. Preferably, the composite cement is a silicate cement and a sulphoaluminate cement in a weight ratio of 15-25:1. In the present invention, the silicate cement is 52.5 grade ordinary silicate cement; the sulphoaluminate cement is 42.5R grade rapid hardening sulphoaluminate cement.
[0009] In the present invention, in the flexural cement, the weight of the gypsum is 20-50 parts. It can be understood that the weight of the gypsum can be any specific value of 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or any value within the range of 20-50 parts. In the present invention, the gypsum is anhydrite.
[0010] In the present invention, in the flexural cement, the weight portion of calcium oxide is 5-15 parts. It can be understood that the weight portion can be any specific value of 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or any value within the range of 5-15 parts.
[0011] In the present invention, in the flexural cement, the weight of the fly ash is 50-60 parts, and it can be understood that the weight can be any specific value of 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts or any value within the range of 50-60 parts. In the present invention, the average particle size of the fly ash is 10-100 μm.
[0012] In the present invention, in the anti-bending cement, the weight portion of the modifier is 4-8 parts. It can be understood that the weight portion can be any specific value of 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or any value within the range of 4-8 parts. In the present invention, the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a mass ratio of 4-8:3-5:1. Preferably, the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a mass ratio of 6-8:4-5:1. In the present invention, the mass percentage of polycarboxylic acid in the polycarboxylic acid grafted graphene oxide is 30-35%. In the present invention, the polycarboxylic acid grafted graphene oxide is obtained by reacting isopentanol polyoxyethylene ether, acrylic acid and graphene oxide. In the present invention, the sheet diameter of the graphene oxide is 0.5-5μm and the thickness is 0.8-1.2nm. Preferably, the average particle size of the nano-SiO2 is 20-80 nm. Preferably, the number average molecular weight of the isopentanol polyoxyethylene ether is 2400 g / mol.
[0013] In the present invention, the modifier prepared by anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a specific mass ratio can significantly improve the flexural properties of cement while taking into account good compressive properties. The reason is that the polycarboxylic acid molecular chain in the polycarboxylic acid grafted graphene oxide is adsorbed and grafted on the surface of the graphene oxide, which has steric hindrance and electrostatic repulsion effects, improves the dispersibility of graphene oxide, in-situ generated calcium aluminate whiskers and cement particles, and at the same time, the addition of a specific amount of anhydrous sodium sulfate and nano-SiO2 fills part of the pores, synergistically improves the density of the structure, thereby improving the flexural properties and compressive properties of cement. The inventor further found that the mass percentage of polycarboxylic acid in the polycarboxylic acid grafted graphene oxide has a key influence on the flexural properties. If the content is too high, the flexural properties will decrease. This is because excessive polycarboxylic acid is grafted on the surface of the graphene oxide, resulting in a decrease in the density of the system, thereby reducing the flexural properties.
[0014] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned anti-flexural cement, comprising the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0015] In the present invention, in the step (1), the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 are mixed in proportion to obtain a modifier. Preferably, the preparation method of polycarboxylic acid grafted graphene oxide comprises the following steps: adding graphene oxide to a first portion of deionized water and stirring thoroughly, adding acrylic acid, isopentanol polyoxyethylene ether, a catalyst and a second portion of deionized water, reacting at 45-55°C for 6-9h, and obtaining the polycarboxylic acid grafted graphene oxide. Preferably, the catalyst is ammonium cerium nitrate. More preferably, the molar ratio of acrylic acid to isopentanol polyoxyethylene ether is 6-8:1, the mass ratio of the first portion of deionized water to the second portion of deionized water is 1:1-1.5, and the molar amount of the catalyst is 0.5-2% of the total molar amount of acrylic acid and isopentanol polyoxyethylene ether.
[0016] In the present invention, in the step (2), the sulphoaluminate cement, gypsum and calcium oxide are mixed in proportion to obtain a first mixture.
[0017] In the present invention, in the step (3), the first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural cement.
[0018] In the present invention, when the anti-flexural cement is used, a certain amount of water is added for preparation and then stirred evenly.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a specific mass ratio to prepare a modifier. The polycarboxylic acid molecular chain in the polycarboxylic acid grafted graphene oxide is adsorbed and grafted on the surface of the graphene oxide, which has a suitable steric hindrance and electrostatic repulsion effect, improves the dispersibility of graphene oxide, in-situ generated calcium aluminate whiskers and cement particles, and at the same time, the addition of a specific amount of anhydrous sodium sulfate and nano-SiO2 fills part of the pores, synergistically improves the density of the structure, achieves good structural regulation, and thus improves the flexural properties of cement. In addition, the addition of the modifier better regulates the hydration rate, thereby improving the early strength of cement-based materials.
[0020] (2) The present invention adds a certain amount of sulphoaluminate cement, gypsum and calcium oxide, which react with each other to generate calcium sulfonate whiskers in situ. These whiskers are evenly dispersed in the silicate cement matrix and are tightly combined with the matrix, promoting the development of its strength, thereby improving the flexural properties of the material.
[0021] (3) The preparation method of the present invention is simple and convenient, the product performance is stable, and it is suitable for large-scale production. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0024] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The invention provides a flexural resistant cement, which comprises the following components by weight: 55-80 parts of compound cement, 20-50 parts of gypsum, 5-15 parts of calcium oxide, 50-60 parts of fly ash and 4-8 parts of a modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a mass ratio of 4-8:3-5:1.
[0027] In the present invention, the composite cement is silicate cement and sulphoaluminate cement in a weight ratio of 13-25:1.
[0028] In the present invention, the mass percentage of polycarboxylic acid in the polycarboxylic acid grafted graphene oxide is 30-35%.
[0029] In the present invention, the silicate cement is 52.5 grade ordinary silicate cement; the sulphoaluminate cement is 42.5R grade rapid hardening sulphoaluminate cement.
[0030] In the present invention, the gypsum is anhydrite.
[0031] In the present invention, the polycarboxylic acid grafted graphene oxide is obtained by reacting isopentanol polyoxyethylene ether, acrylic acid and graphene oxide.
[0032] In the present invention, the average particle size of the fly ash is 10-100 μm.
[0033] In the present invention, the average particle size of the nano-SiO2 is 20-80nm.
[0034] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned anti-flexural cement, comprising the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0035] In the present invention, the preparation method of the polycarboxylic acid grafted graphene oxide comprises the following steps: adding graphene oxide to a first portion of deionized water and stirring the mixture sufficiently, adding acrylic acid, isopentanol polyoxyethylene ether, a catalyst and a second portion of deionized water, and reacting the mixture at 45-55° C. for 6-9 hours to obtain the polycarboxylic acid grafted graphene oxide.
[0036] The present invention will be described in detail below by way of examples. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not intended to limit the present invention. Among them, Example 1 is the best embodiment of the present invention.
[0037] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows: Sulphoaluminate cement: 42.5R grade fast-hardening sulphoaluminate cement, purchased from Wuxi Jianghuai Building Materials Co., Ltd.; Portland cement: 52.5 grade ordinary Portland cement, purchased from Wuxi Jianghuai Building Materials Co., Ltd.; Gypsum: hard gypsum, purchased from Hubei Longyuan Gypsum Co., Ltd.; Calcium oxide: purchased from Zibo Wanpu New Materials Co., Ltd.; Graphene oxide: sheet diameter of 0.5-5μm, thickness of 0.8-1.2nm, purchased from Aladdin Reagent Co., Ltd.; Nano-SiO2: average particle size of 20-80nm, purchased from Aladdin Reagent Co., Ltd.; Anhydrous sodium sulfate, acrylic acid, isopentanol polyoxyethylene ether (number average molecular weight 2400g / mol), ammonium cerium nitrate: all purchased from Aladdin Reagent Co., Ltd.; Fly ash: average particle size of 10-100μm, purchased from Guangdong Xinze Building Materials Co., Ltd.; Water: ordinary tap water.
[0038] Polycarboxylic acid grafted graphene oxide A: The preparation method of the polycarboxylic acid grafted graphene oxide comprises the following steps: adding 48.9 g of graphene oxide to 600 mL of the first part of deionized water and stirring thoroughly, adding 4 g of acrylic acid, 19 g of isopentanol polyoxyethylene ether, 0.35 g of catalyst ammonium cerium nitrate and 900 mL of the second part of deionized water, introducing nitrogen, reacting at 55° C. for 6 hours, and obtaining the polycarboxylic acid grafted graphene oxide A.
[0039] Polycarboxylic acid grafted graphene oxide B: The preparation method of the polycarboxylic acid grafted graphene oxide comprises the following steps: adding 48.3 g of graphene oxide to 600 mL of the first part of deionized water and stirring thoroughly, adding 4 g of acrylic acid, 16.7 g of isopentanol polyoxyethylene ether, 0.69 g of catalyst ammonium cerium nitrate and 600 mL of the second part of deionized water, introducing nitrogen, reacting at 50° C. for 9 hours, and obtaining the polycarboxylic acid grafted graphene oxide B.
[0040] Polycarboxylic acid grafted graphene oxide C: The preparation method of the polycarboxylic acid grafted graphene oxide comprises the following steps: adding 42.7 g of graphene oxide to 600 mL of the first part of deionized water and stirring thoroughly, adding 4 g of acrylic acid, 19 g of isopentanol polyoxyethylene ether, 0.35 g of catalyst ammonium cerium nitrate and 700 mL of the second part of deionized water, introducing nitrogen, reacting at 55° C. for 6 hours, and obtaining the polycarboxylic acid grafted graphene oxide C.
[0041] Polycarboxylic acid grafted graphene oxide D: The preparation method of the polycarboxylic acid grafted graphene oxide comprises the following steps: adding 34.5 g of graphene oxide to 600 mL of the first part of deionized water and stirring thoroughly, adding 4 g of acrylic acid, 19 g of isopentanol polyoxyethylene ether, 0.35 g of catalyst ammonium cerium nitrate and 700 mL of the second part of deionized water, introducing nitrogen, reacting at 55° C. for 6 hours, and obtaining the polycarboxylic acid grafted graphene oxide D.
[0042] The polycarboxylic acid grafted graphene oxide prepared above was subjected to thermogravimetric analysis, and the specific method was as follows: 20 mg of the sample was weighed into a crucible, and the crucible was placed on the sample stage of the thermal analyzer. Under a nitrogen atmosphere, the sample was heated from room temperature 25°C to 1000°C at a heating rate of 10°C / min. The content of polycarboxylic acid was calculated according to the thermogravimetric analysis curve, and the specific results are shown in Table 1.
[0043] Table 1 Performance data of polycarboxylic acid grafted graphene oxide .
[0044] Example 1 The flexural cement described in this embodiment includes the following components in parts by weight: 60 parts of compound cement, 25 parts of gypsum, 15 parts of calcium oxide, 55 parts of fly ash and 6 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide A and nano-SiO2 in a mass ratio of 6:4:1; the compound cement is silicate cement and sulphoaluminate cement in a weight ratio of 19:1.
[0045] The preparation method of the anti-flexural cement comprises the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide A and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0046] Example 2 The flexural cement described in this embodiment includes the following components, measured in parts by weight: 55 parts of compound cement, 32 parts of gypsum, 15 parts of calcium oxide, 60 parts of fly ash and 8 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide B and nano-SiO2 in a mass ratio of 4:3:1; the compound cement is silicate cement and sulphoaluminate cement in a weight ratio of 13:1.
[0047] The preparation method of the anti-flexural cement comprises the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide B and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0048] Example 3 The flexural cement described in this embodiment includes the following components in parts by weight: 80 parts of compound cement, 20 parts of gypsum, 12 parts of calcium oxide, 50 parts of fly ash and 4 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide C and nano-SiO2 in a mass ratio of 8:5:1; the compound cement is silicate cement and sulphoaluminate cement in a weight ratio of 25:1.
[0049] The preparation method of the anti-flexural cement comprises the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide C and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0050] Example 4 The flexural cement described in this embodiment includes the following components in parts by weight: 66 parts of compound cement, 20 parts of gypsum, 15 parts of calcium oxide, 50 parts of fly ash and 7 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide A and nano-SiO2 in a mass ratio of 4:3:1; the compound cement is silicate cement and sulphoaluminate cement in a weight ratio of 15:1.
[0051] The preparation method of the anti-flexural cement comprises the following steps: (1) mixing the anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide A and nano-SiO2 in proportion to obtain a modifier; (2) mixing the sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain the flexural resistant cement.
[0052] Comparative Example 1 The preparation method of the anti-bending cement described in this comparative example is the same as that of Example 1, except that the polycarboxylic acid grafted graphene oxide A is replaced by an equal amount of polycarboxylic acid grafted graphene oxide D.
[0053] Comparative Example 2 The preparation method of the flexural-resistant cement described in this comparative example is the same as that of Example 1, except that the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide A and nano-SiO2 in a mass ratio of 5:8:1.
[0054] Comparative Example 3 The preparation method of the high-performance cement-based grouting material described in this comparative example is the same as that of Example 1, except that the modifier is polycarboxylic acid grafted graphene oxide A and nano-SiO2 in a mass ratio of 4:1.
[0055] Comparative Example 4 The preparation method of the flexural-resistant cement described in this comparative example is the same as that of Example 1, except that the composite cement is silicate cement and sulphoaluminate cement in a weight ratio of 35:1.
[0056] Performance Testing The cement, sand and water described in Examples 1-4 and Comparative Examples 1-4 were prepared with a water-cement ratio of 0.4 and a mass ratio of cement to sand of 1:3. After being stirred evenly, the paste was taken out and placed in a mold (40 mm × 40 mm × 160 mm), and then maintained in a constant temperature and humidity chamber at 25°C and 98% for 28 days. The performance test was carried out in accordance with standard GB / T17671-2021, and the specific results are shown in Table 2.
[0057] Table 2 Cement performance data in Examples 1-4 and Comparative Examples 1-4 .
[0058] It can be seen from Table 1 that the flexural strength and compressive strength of the cement described in Examples 1-4 of the present invention are relatively high at different days, among which the 3d flexural strength of the cement in Example 1 exceeds 20MPa, the 7d flexural strength exceeds 33MPa, and the 28d flexural strength exceeds 39MPa, indicating that its early and long-term flexural strengths are relatively high. By comparing Example 1 with Comparative Example 1, it can be seen that the content of polycarboxylic acid in the polycarboxylic acid grafted graphene oxide in Comparative Example 1 is relatively high, and its flexural strength and compressive strength are significantly reduced, indicating that the content of polycarboxylic acid in the polycarboxylic acid grafted graphene oxide has a greater influence on the mechanical properties of the cement system, and the more content, the better. It can be seen from Example 1 and Comparative Example 2 that the proportion of polycarboxylic acid grafted graphene oxide in the modifier in Comparative Example 2 is relatively high, and its flexural strength is significantly reduced, indicating that the ratio relationship of the three components in the modifier is critical to the flexural performance, and the change in ratio will reduce the synergistic effect of the three, thereby affecting the performance. It can be seen from Example 1 and Comparative Example 3 that the modifier in Comparative Example 3 does not contain anhydrous sodium sulfate, and its flexural strength is significantly reduced, indicating that there is a synergistic effect between the three components in the modifier, which jointly improves the flexural strength of the system. It can be seen from Example 1 and Comparative Example 4 that the composite ratio of silicate cement and sulphoaluminate cement in Comparative Example 4 is different, and the compressive strength and flexural strength of the system are affected.
[0059] It can be seen that the present invention adopts anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a specific mass ratio to prepare a modifier. The polycarboxylic acid molecular chain in the polycarboxylic acid grafted graphene oxide is adsorbed and grafted on the surface of the graphene oxide, which has a suitable steric hindrance and electrostatic repulsion effect, and can improve the dispersibility of graphene oxide, calcium aluminate whiskers generated in situ in the system and cement particles. At the same time, the addition of a specific amount of anhydrous sodium sulfate and nano-SiO2 fills part of the pores, synergistically improves the compactness of the structure, and achieves good structural regulation, thereby improving the bending resistance of cement. The addition of the modifier better regulates the hydration rate. The hydration rate and pore structure of the cement described in the present invention avoid cracking damage caused by freezing of water in the pore structure at low temperatures, thereby improving the early strength and low temperature resistance of cement-based materials. In addition, the present invention adds a certain amount of sulphoaluminate cement, gypsum and calcium oxide, and the three react with each other to generate calcium sulfonate whiskers in situ. These whiskers are evenly dispersed in the silicate cement matrix and tightly combined with the matrix, playing a bridging role, promoting the development of its strength, thereby improving the material's flexural resistance.
[0060] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A flexural cement, characterized in that: The invention comprises the following components by weight: 55-80 parts of compound cement, 20-50 parts of gypsum, 5-15 parts of calcium oxide, 50-60 parts of fly ash and 4-8 parts of modifier; wherein the modifier is anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in a mass ratio of 4-8:3-5:
1.
2. The flexural cement according to claim 1, characterized in that: The composite cement is silicate cement and sulphoaluminate cement in a weight ratio of 13-25:
1.
3. The flexural cement according to claim 1, characterized in that: In the polycarboxylic acid grafted graphene oxide, the mass percentage of polycarboxylic acid is 30-35%.
4. The flexural-resistant cement according to claim 2, characterized in that: The silicate cement is 52.5 grade ordinary silicate cement; the sulphoaluminate cement is 42.5R grade rapid hardening sulphoaluminate cement.
5. The flexural-resistant cement according to claim 1, characterized in that: The gypsum is anhydrite.
6. The flexural-resistant cement according to claim 1, characterized in that: The polycarboxylic acid grafted graphene oxide is obtained by reacting isopentanol polyoxyethylene ether, acrylic acid and graphene oxide.
7. The flexural-resistant cement according to claim 1, characterized in that: The average particle size of the fly ash is 10-100 μm.
8. The flexural-resistant cement according to claim 1, characterized in that: The average particle size of the nano-SiO2 is 20-80nm.
9. A method for preparing the flexural-resistant cement according to any one of claims 1 to 8, characterized in that: The steps include: (1) mixing anhydrous sodium sulfate, polycarboxylic acid grafted graphene oxide and nano-SiO2 in proportion to obtain a modifier; (2) mixing sulphoaluminate cement, gypsum and calcium oxide in proportion to obtain a first mixture; (3) The first mixture, silicate cement, fly ash and modifier are mixed in proportion to obtain flexural cement.
10. The method for preparing flexural resistant cement according to claim 9, characterized in that: The preparation method of polycarboxylic acid grafted graphene oxide comprises the following steps: adding graphene oxide to a first portion of deionized water and stirring the mixture thoroughly, adding acrylic acid, isopentanol polyoxyethylene ether, a catalyst and a second portion of deionized water, and reacting the mixture at 45-55° C. for 6-9 hours to obtain the polycarboxylic acid grafted graphene oxide.
Citation Information
Patent Citations
A high compressive and high flexural strength cement, composite material, and molding method synergistically reinforced with micron-sized silicon carbide and micro-steel fibers.
CN109678402B
A high flexural strength composite silicate cement and its preparation method
CN110436801B
Portland cement-sulphate aluminum cement-gypsum-polymer composite waterproof mortar and preparation method thereof
CN103951365A
Low-expansion cement
CN109626938A
High-performance cement-based grouting material and preparation method thereof
CN118359415A